2020
DOI: 10.1038/s41598-020-78360-9
|View full text |Cite
|
Sign up to set email alerts
|

Absence of relevant QT interval prolongation in not critically ill COVID-19 patients

Abstract: SARS-CoV-2 is a rapidly evolving pandemic causing great morbimortality. Medical therapy with hydroxicloroquine, azitromycin and protease inhibitors is being empirically used, with reported data of QTc interval prolongation. Our aim is to assess QT interval behaviour in a not critically ill and not monitored cohort of patients. We evaluated admitted and ambulatory patients with COVID-19 patients with 12 lead electrocardiogram at 48 h after treatment initiation. Other clinical and analytical variables were colle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…Furthermore, a good prognosis has been reported in patients without an increase in the QT interval. 22) There have also been reports of prolonged QT in patients whose myocarditis was demonstrated by myocardial biopsy. 23) Based on this study's results, the longest QT interval was more prolonged as disease severity worsened.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a good prognosis has been reported in patients without an increase in the QT interval. 22) There have also been reports of prolonged QT in patients whose myocarditis was demonstrated by myocardial biopsy. 23) Based on this study's results, the longest QT interval was more prolonged as disease severity worsened.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 QT-interval prolongation, which is associated with ventricular arrhythmias, has been reported as side effect of hydroxychloroquine in studies in both SARS-CoV-2 patients and patients with other conditions. 19,[40][41][42] Previous studies found a prolongation of the QTcF-interval after hydroxychloroquine administration from 424.4 ±29.7 ms at baseline to 432.0 ±32.3 ms in rheumatologic patients 43 , and from 416 (IQR 404 -433) to 423 (IQR 405 -438) ms in SARS-CoV-2 patients. 40 Another study in SARS-CoV-2 patients reported an increase of 13 (IQR 9 -16) ms. 41 Other studies reported QTcF-prolongation after hydroxychloroquine treatment only in a minority of their cases.…”
Section: Discussionmentioning
confidence: 99%
“…19,[40][41][42] Previous studies found a prolongation of the QTcF-interval after hydroxychloroquine administration from 424.4 ±29.7 ms at baseline to 432.0 ±32.3 ms in rheumatologic patients 43 , and from 416 (IQR 404 -433) to 423 (IQR 405 -438) ms in SARS-CoV-2 patients. 40 Another study in SARS-CoV-2 patients reported an increase of 13 (IQR 9 -16) ms. 41 Other studies reported QTcF-prolongation after hydroxychloroquine treatment only in a minority of their cases. 44,45 E.g., an average increase of the QTcF-interval of 1.8% was observed in a cohort of 219 hospitalized and ambulatory SARS-CoV-2 patients who were treated with a total dose of 2800 mg hydroxychloroquine, although combined with other antiviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In our center, we developed a smartwatch electrocardiogram and artificial intelligence for assessing the cardiac rhythm safety of HCQ+AZ and did not find any QTc prolongation [35]. In the literature, ambulatory and not critically ill patients with COVID-19 treated with hydroxychloroquine, azithromycin and/or antiretrovirals develop a significant, but not relevant, QT interval prolongation [36]. As shown in our cohort, a simple clinical and biological evaluation with blood potassium assessment and the use of a first electrocardiogram allowed us to initiate treatment with acceptable safety in terms of potential arrhythmias.…”
Section: Discussionmentioning
confidence: 91%